Blue hydrogen as an enabler of green hydrogen: The case of Germany - Ralf Dickel (The Oxford Institute for Energy Studies, 2020)
In Germany decarbonization of the electricity sector by fostering renewables and now phasing out coal-fired power is on track to reach the 2050 de-carbonisation targets, while decarbonising non-electric energy consumption is proving to be more difficult. The present discussion of a national hydrogen strategy has run into strong political opposition against carbon sequestration as a necessary element in the use of decarbonized natural gas (blue hydrogen), and is aiming at the use of green hydrogen only (from renewable electricity and electrolysis). This paper shows that as long as the power sector is not decarbonized – not likely before 2040 – only marginal volumes of renewable electricity will be available to produce green hydrogen. To meet the decarbonization target by 2050 blue hydrogen has to fill that gap, paving the way for green hydrogen at a later stage. The paper discusses the elements needed for an expedient development of blue hydrogen. It also points at the need, and instruments, to decarbonize core industries like the steel and chemical industry so that they can become future proof in competition with the US, which is more advanced with a decarbonization strategy for its industry based on carbon sequestration.
Keywords: 330; carbon sequestration; decarbonization; methane blending; Paris Agreement; public good; renewable electricity; steam reforming